Threshold of spontaneous emission amplification by relativistic electron beam in undulator - Ognivenko, V.V. (Вопросы атомной науки и техники, 2008)
Motion of a relativistic beam of electrons through an undulator is considered, with the influence of incoherent
fields its spontaneous radiation on this motion being taken into aсcount. Interaction of electrons with these fields is
shown to result in the increase of electron-momentum spread in the beam. The conditions of high-gain self-amplified
spontaneous emission process realization in the ultrashort-wavelength FELs are discussed Розглянуто рух релятивістського пучка електронів в ондуляторі з урахуванням впливу на цей рух некогерентних полів їхнього спонтанного випромінювання. Показано, що взаємодія електронів із цими полями призводить до збільшення розкиду електронів по імпульсах у пучку. Обговорюються умови реалізації процесу інтенсивного самочинного підсилення спонтанного випромінювання в ультракороткохвильових ЛВЕ. Рассмотрено движение релятивистского пучка электронов в ондуляторе с учетом влияния на это движение некогерентных полей их спонтанного излучения. Показано, что взаимодействие электронов с этими полями приводит к увеличению разброса электронов по импульсам в пучке. Обсуждаются условия реализации процесса интенсивного самопроизвольного усиления спонтанного излучения в ультракоротковолновых ЛСЭ.